Perovskite-like LaNiO3-δ as Oxygen Electrode Material for Solid Oxide Electrolysis Cells. (10th July 2019) - Yaremchenko, Aleksey; Arias-Serrano, Blanca I.; Zakharchuk, Kiryl; Frade, Jorge R.
Abstract : Perovskite-like LaNiO3-δ was evaluated as potential oxygen electrode material for solid oxide electrolysis cells. Compared to the Ruddlesden-Popper Lan+1 Nin O3n+1 (n = 1, 2, 3) counterparts, LaNiO3-δ exhibits higher p -type metallic-like conductivity under oxidizing conditions (450 S×cm -1 at 800°C for highly porous ceramics) together with a moderate thermal expansion coefficient (13.7 ppm×K -1 in air at 25-800°C) compatible with common solid electrolytes. The measured electrode polarization resistance (Rη ) in contact with YSZ, CGO and LSGM solid electrolytes was 1.4, 0.77 and 0.22 Ω×cm 2 at 800°C, and 208, 123 and 7.1 Ω×cm 2 at 600°C, respectively, under zero-current conditions in air. Surface modification of via PrO x infiltration resulted in lower values of Rη (0.024 Ω×cm 2 at 800°C and 0.76 Ω×cm 2 at 600°C) and low anodic overpotentials (20 mV at 800°C and 500 mA×cm -2 ) in contact with LSGM.